The act of abortion due to rape in the view of ath-tabari in kitab jami' al-bayan fi ta'wil Al-qur'an - Eztika Azzahra Aji; Ahmad Zuhri; Husnel Anwar Matondang; Mardian Idris Harahap (Jurnal Educatio: Jurnal Pendidikan Indonesia)
The aim of this research is to provide insight to readers regarding what is meant by abortion as discussed in Ath-tabari's view in the book Jami-al-Bayan fi Ta'wil. Abortus provocatus medicinalis is an abortion carried out based on medical reasons/considerations. Meanwhile, abortion provocatus criminalis is an abortion carried out intentionally in violation of applicable legal provisions. Medically defines abortion as a pregnancy that terminates before the gestational age reaches 20 weeks and then results in the death of the fetus. When the fetus is alive or born safely after 20 weeks and before 38 weeks, it is called premature birth because the minimum period of pregnancy is 6 months and 20 weeks means not yet 6 months. The research method in this research is to use a type of library research method, namely by searching for data from various literature related to sexual violence and its prevention. Using content analysis methods, this research describes interpreters' interpretations of how the Koran prohibits sexual violence and provides ways to prevent it. The conclusion of this research is that the view of Islamic Sharia generally prohibits the practice of abortion. This is not permitted for several reasons, namely Islamic Sharia came in order to maintain Adhdharuriyyaat al-khams, abortion is completely contrary to the main purpose of marriage and the act of abortion is a negative attitude towards Allah SWT. The act of abortion is a negative attitude towards God. One will find many people who have abortions because they are driven by fear of being unable to carry the burden of life, educational costs and all matters related to counseling and child care. These are all negative attitudes towards Allah.